Identification of human papillomavirus type 156, the prototype of a new human gammapapillomavirus species, by a generic and highly sensitive PCR strategy for long DNA fragments - Chouhy, Diego (2013)
This study developed a hanging-droplet long PCR, a generic and highly sensitive strategy to facilitate the identification of new human papillomavirus (HPV) genomes. This novel procedure used for the first time the hanging-droplet PCR technique for the amplification of long DNA fragments with generic primers targeting the L1 and E1 regions. It was first applied to the amplification of types belonging to the highly divergent genus Gammapapillovirus (Gamma-PV). The hanging-droplet long PCR was 100-fold more sensitive than a simple long PCR procedure, detecting as few as ten copies of HPV-4. Nineteen skin samples, potentially containing putative HPV types from the gamma-PV genus, were also screened. The method identified four γ-PV genomic halves from new and previously described putative types, and made the full characterization of HPV-156 possible. This novel virus meets the criteria for a new species within the gamma-PV genus, with nucleotide identities in the L1 ORF ranging from 58,3 to 67,3% compared with representative types of the current γ-PV species. HPV-156 showed the highest identity to HPV-60 (67,3%) from species gamma-4, and was consistently closely related to it in both late- and early-gene-derived phylogenies. In conclusion, this report provides a versatile and highly sensitive approach that allowed identification of the prototype of a new species within the γ-PV genus. Its application with primers targeting the different genera in which both human and non-human PVs are distributed may facilitate characterization of the missing members of the family Papillomaviridae.